Power over life: a study about the representation of women and their dilemmas facing slavery in the 19th century in ‘Kindred’ by Octavia Butler - NASCIMENTO, Juliana Souza (2023)
This paper aims to discuss the book "Kindred" by the American science fiction author Octavia Butler. Here we aim to analyze the work from the perspective of how power has influence over the life of the enslaved population. For this discussion, we will make an analysis divided into two parts. In the first one we will use Achillie Mbembe's theory of necropolitics to understand how the narrative demonstrates how death is used as a tool to control the lives of certain subjects. Subsequently, we intend to analyze the work from the female perspective, because within the book it is possible to recognize the racism, prejudice, and barbarities committed against the black people during the slavery period, but we can also notice that the enslaved women end up experiencing several other sufferings such as sexual exploitation and the objectification of her body. To achieve this goal we will use the theory of Angela Davis in her work 'Women, Race, and Class' (1983) in which the author discusses how the enslaved women suffered other types of violence, in addition to those already imposed on the enslaved population. To develop this research we chose to work with qualitative research and bibliographical research. When we read Kindred, we tried to identify at which points the events in the work of fiction are connected to the reality lived by the slaves and relate them to the theories of the chosen authors. With this work we aim to contribute to studies in the field of literature and necropolitics.